Pyqt5-Based Alpha Energy Spectrum Analysis Software - Liu, Minjun; Shi, Rui; Wang, Bo; Wang, Zhou; Zeng, Xiong (International Journal of Computer Science and Information Technology, 2024)
The alpha energy spectrum measurement is a very important nuclear radiation measurement method. In order to acquire and process and analyze the alpha energy spectrum on-line, it is necessary to cooperate with a well-functioning, easy-to-operate, and interactive and friendly energy spectrum analysis software. The software uses a PIPS (Passivated Implanted Planar Silicon) detector, which has the advantages of high energy resolution, low noise and excellent spatial resolution compared with the traditional semiconductor Si detector, and a set of α energy spectrum analysis software system is designed and developed based on the framework of PyQt5, which realizes the online acquisition and processing of the α spectrum data, and smooths the data. Based on PyQt5 framework, a software system for α energy spectrum analysis was designed and developed to realize the online acquisition of α energy spectrum data, and to realize the functions of smoothing, energy scale, peak searching, peak area calculation, etc. After experimental testing, the software realizes the important methods of α energy spectrum analysis and energy spectrum decomposition, and the human-computer interaction is friendly, with good practicability and maintainability, and it has a certain value of use.